Undergraduate research: eliminating the drinking from the firehouse effect. - Anandhi, Aavudai; Baker, Lauri M. (My University, 2013)
Including undergraduates in research is an increasing trend in many programs of agriculture and natural resources across the United States. As teachers we struggle with how to introduce the most important concepts without overwhelming students in the process. Aavudai Anandhi, an assistant professor of agronomy at Kansas State University, developed a technique to understand complex topics when reading secondary research. She developed this technique in order to help her when researching for her dissertation, but she has continued using the technique herself and teaching students in her lab the technique too. She has noticed that students grasp the major concepts quicker and are able to interpret what they are reading better. This has resulted in her ability to keep students working in her lab for longer, because they feel empowered by understanding the purpose in what they are doing.
Teaching undergraduate researchers: eliminating the drinking from the fire hose effect
Citation: Anandhi, A., & Baker, L. M. (2013). Undergraduate research: Eliminating the drinking from the firehouse effect. Retrieved from http://krex.ksu.edu
Keywords: Undergraduate research; Secondary research; Teaching; Literature review